Associations of Gestational Weight Gain at Different Trimesters with Adverse Pregnancy Outcomes. A Prospective Study of 1273 Subjects - Xue-Mei Cai; Qiu-Qi Huang; Ting Zhang; Yue Liu; Jian-Lin Fu; Jun-Yu Chen; Ru-Yu Ren; Ni Ren; Xin-Yang Yu; Yin-Yin Xia; Ting-Li Han; Chang Chen; et al. (Clinical and Experimental Obstetrics & Gynecology, 2023)
Background: The incidence of excessive weight gain during pregnancy continues to increase. Our aim was to compare pregnancy outcomes at different trimesters and different classification criteria of gestational weight gain (GWG) and to examine whether GWG was correlated with adverse outcomes in the population of Southwest China. Methods: In the randomized controlled trial of Complex Lipids in Mothers and Babies (CLIMB) conducted in Chongqing, China, data from 1273 women was analyzed. We used two criteria to define GWG as insufficient, appropriate or excessive. The first was based on Chinese, Asian, European Body Mass Index (BMI) and US Institute of Medicine (IOM) guidelines. The second was based on the quantiles of GWG of the subjects studied. Results: After adjusting for confounding factors, excessive GWG during gestational periods 12–33 weeks and 12 weeks to delivery was linked to the occurrence of large for gestational age (LGA) infants. The 12 weeks to delivery group was linked to the occurrence of macrosomia, and all periods studied (12–33 weeks, 12 weeks to delivery, and 33 weeks to delivery) were associated with an increased incidence of C-section. Insufficient GWG during 12–33 weeks was associated with the occurrence of small gestational age (SGA) infants. Conclusions: Our results support that inappropriate GWG during specific gestational periods was associated with an increased risk of adverse pregnancy outcomes among women in southwestern China. Clinical Trial Registration: Clinical Trial Registration number ChiCTR-IOR-16007700.